Detection of β-lactoglobulin in human breast-milk 7 days after cow milk ingestion. (3rd July 2017) - Matangkasombut, Ponpan; Padungpak, Savitree; Thaloengsok, Sasikanya; Kamchaisatian, Wasu; Sasisakulporn, Cherapat; Jotikasthira, Wanlapa; Benjaponpitak, Suwat; Manuyakorn, Wiparat
Abstract: Background : β-lactoglobulin (BLG), a major allergen in cow milk (CM) can be detected in human breast-milk (BM) and is associated with exacerbation of symptoms in breastfed infants with cow milk protein allergy (CMPA). Currently, it is not known how long lactating mothers who consume dairy products need to withhold breastfeeding. Objective: To elucidate the kinetics of BLG in BM after maternal ingestion of a single dose of CM. Methods: Nineteen lactating mothers, four of whom had infants with CMPA, were instructed to avoid CM for 7 days before ingesting a single dose of CM and to continue to withhold CM thereafter throughout the study period. BLG was measured by ELISA in BM from 15 mothers of healthy infants before and at 3, 6 and 24 h, and 3 and 7 days after CM ingestion. Four pairs of mothers and CMPA infants were enrolled for BM challenge after the mothers had ingested CM. Results: After CM ingestion, the level of BLG in BM increased significantly from 0.58 ng/ml (0.58 g/L) (IQR 0.38–0.88) to a peak level of 1.23 ng/ml (IQR 1.03–2.29), p  < 0.001. The BLG level on day 3 (1.15 ng/ml, IQR 0.89–1.45) and day 7 (1.08 ng/ml (IQR 0.86–1.25) after CM ingestion was significantly higher than baseline ( p  = 0.01 and p  = 0.001, respectively). BLG was detected in all BM samples from the four mothers of CMPA infants after CM ingestion, and the level was not different from that in the mothers of the 15 healthy infants. Three of the four CMPA infants developed symptoms such as maculopapular rash and hypersecretion in the airways after BM challenge. Conclusions: BLG can be detected in BM up to 7 days after CM ingestion. Lactating mothers should suspend breastfeeding to CMPA infants more than 7 days after CM ingestion.